2010
DOI: 10.1186/1471-2318-10-14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginkgo biloba in dementia: systematic review and meta-analysis

Abstract: BackgroundThe benefit of Ginkgo biloba has been discussed controversially. The aim of this review was to assess the effects of Ginkgo biloba in Alzheimer's disease as well as vascular and mixed dementia covering a variety of outcome domains.MethodsWe searched MEDLINE, EMBASE, the Cochrane databases, CINAHL and PsycINFO for controlled trials of ginkgo for Alzheimer's, vascular or mixed dementia. Studies had to be of a minimum of 12 weeks duration with at least ten participants per group. Clinical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
139
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(152 citation statements)
references
References 48 publications
7
139
0
5
Order By: Relevance
“…No entanto, seus benefícios à saúde humana, em particular sobre a demência e deficiên-cia cognitiva, não foram totalmente estabelecidas 40 . Estudo recente verificou melhora de cognição entre pacientes com Alzheimer e demên-cia vascular ou mista associada do uso do Ginkgo biloba 41 . Puppo & Silva 42 alertam para os riscos das possíveis interações entre o Ginkgo biloba e o AAS, comumente utilizado pelos idosos, porque essa associação, por aumentar a inibição da agregação plaquetária, pode causar hemorragias, representando riscos para a saúde do idoso.…”
Section: Discussionunclassified
“…No entanto, seus benefícios à saúde humana, em particular sobre a demência e deficiên-cia cognitiva, não foram totalmente estabelecidas 40 . Estudo recente verificou melhora de cognição entre pacientes com Alzheimer e demên-cia vascular ou mista associada do uso do Ginkgo biloba 41 . Puppo & Silva 42 alertam para os riscos das possíveis interações entre o Ginkgo biloba e o AAS, comumente utilizado pelos idosos, porque essa associação, por aumentar a inibição da agregação plaquetária, pode causar hemorragias, representando riscos para a saúde do idoso.…”
Section: Discussionunclassified
“…[78] Ginkgo supplements are usually taken in the range of 40-200 mg per day. In 2010, a meta-analysis of clinical trials has shown Ginkgo to be moderately effective in improving cognition in dementia patients [79] but not preventing the onset of Alzheimer's disease in people without dementia. [80,81] Ginkgo is believed to have no tropic properties, and is mainly used as memory and concentration enhancer, and antivertigo agent.…”
Section: Ginkgo Biloba (Maidenhair Tree)mentioning
confidence: 99%
“…The standardized extract of this herb, EGb 761, is prescribed as a dietary supplement and is touted to have neuroprotective and neurorestorative properties that have been consistently reproduced in many animal models of CNS disorders (Kehr et al, 2012; Diamond and Bailey, 2013; Tulsulkar and Shah, 2013; Wang et al, 2013a). Its use as a symptomatic treatment for dementia has been established in many preclinical studies (Tchantchou et al, 2007; Wang et al, 2013b) and clinical trials (Oken et al, 1998; Schneider et al, 2005; Mazza et al, 2006; Weinmann et al, 2010). A number of clinical studies conducted in Europe and the US have demonstrated the potential therapeutic effects of G. biloba in multi-infarct dementia, early or mild cognitive decline, and severe types of senile dementias (Weinmann et al, 2010; Amieva et al, 2013).…”
mentioning
confidence: 99%
“…Its use as a symptomatic treatment for dementia has been established in many preclinical studies (Tchantchou et al, 2007; Wang et al, 2013b) and clinical trials (Oken et al, 1998; Schneider et al, 2005; Mazza et al, 2006; Weinmann et al, 2010). A number of clinical studies conducted in Europe and the US have demonstrated the potential therapeutic effects of G. biloba in multi-infarct dementia, early or mild cognitive decline, and severe types of senile dementias (Weinmann et al, 2010; Amieva et al, 2013). However, “Ginkgo Evaluation of Memory (GEM),” showed no effect of EGb 761 (240 mg daily dose for 7 years) on delaying or preventing Alzheimer’s-related dementia among the population aged 75 or older (DeKosky et al, 2006).…”
mentioning
confidence: 99%